Bowling Performance Assessed with a Smart Cricket Ball: A Novel Way of Profiling Bowlers - Franz Konstantin Fuss; Batdelger Doljin; René E. D. Ferdinands (Proceedings, 2020)
Profiling of spin bowlers is currently based on the assessment of translational velocity and spin rate (angular velocity). If two spin bowlers impart the same spin rate on the ball, but bowler A generates more spin rate than bowler B, then bowler A has a higher chance to be drafted, although bowler B has the potential to achieve the same spin rate, if the losses are minimized (e.g., by optimizing the bowler’s kinematics through training). We used a smart cricket ball for determining the spin rate and torque imparted on the ball at a high sampling frequency. The ratio of peak torque to maximum spin rate times 100 was used for determining the ‘spin bowling potential’. A ratio of greater than 1 has more potential to improve the spin rate. The spin bowling potential ranged from 0.77 to 1.42. Comparatively, the bowling potential in fast bowlers ranged from 1.46 to 1.95.